2018
DOI: 10.5897/ijbc2018.1226
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of soil seed banks: Implications for conservation and restoration of natural vegetation: A review

Abstract: Seed bank (henceforth referred to as SB) refers to viable seed which is present on or in soil and associated with litter/humus. Under different land use/land cover systems and climatic regions, density of seeds in the soil is variable both in space and time. SB density decreases with increasing depth and age of seeds in the soil. Smaller seeds are more easily incorporated, moved to deeper soil layers and persist longer in the soil, whereas large sized seeds without hard seed coats lack persistence in the soil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…Expression of a weedy seedbank may hinder native ecosystem recovery, following the removal of invasive species or during the restoration of ex‐arable lands, where native plant species may fail to establish or persist in the face of intense weed competition (e.g., Holl et al, 2000; Cramer et al, 2008). Soil seed banks may also house species of high conservation interest, whose persistence in the soil through periods of degradation may assist passive ecosystem recovery once appropriate conditions are reinstated through management (Bakker et al, 1996; Shiferaw et al, 2018). Although our results provide fewer direct insights for these types of species, they suggest promise for long‐term persistence in the soil seed bank for at least a subset of conservation‐relevant plant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of a weedy seedbank may hinder native ecosystem recovery, following the removal of invasive species or during the restoration of ex‐arable lands, where native plant species may fail to establish or persist in the face of intense weed competition (e.g., Holl et al, 2000; Cramer et al, 2008). Soil seed banks may also house species of high conservation interest, whose persistence in the soil through periods of degradation may assist passive ecosystem recovery once appropriate conditions are reinstated through management (Bakker et al, 1996; Shiferaw et al, 2018). Although our results provide fewer direct insights for these types of species, they suggest promise for long‐term persistence in the soil seed bank for at least a subset of conservation‐relevant plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the composition and dynamics of seed banks is important in major aspects of plant ecology and evolution (Levin, 1990; Maron and Simms, 1997; Evans et al, 2007; Yamamichi et al, 2019). Beyond basic science, the study of seed banks is of central concern for agricultural weed management, invasive species management, ecosystem restoration, fire ecology, and the conservation of rare and threatened species (Baskin and Baskin, 1998; Shiferaw et al, 2018; Pausas and Lamont, 2022). However, despite their importance, we still have a poor understanding of soil seed banks due to the logistical challenges inherent in their study.…”
Section: Date 1884 1889 1894 1899 1904 1909 1914 1920 1930 1940 1950 ...mentioning
confidence: 99%
“…Many studies have shown that knowledge about the soil seed bank and its potential for recolonization of eroded or otherwise degraded sites is of crucial importance for ecosystem restoration (Wellstein et al 2007; Bossuyt & Honnay 2008; Shiferaw et al 2018). However, soil seed bank analysis is labor intensive and thus of low popularity.…”
Section: Introductionmentioning
confidence: 99%
“…However, soil seed bank analysis is labor intensive and thus of low popularity. Nonetheless, the soil seed bank has been proven to be an important factor in nature conservation and ecosystem restoration research and practice (Middleton 2003; Shiferaw et al 2018; Shi et al 2020). Particularly, the restoration potential of specific vegetation communities can be assessed (Kalamees et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Seed banks are known for their ability in maintaining a gene pool, which allows plants to continuously occupy a site after disturbance through a mechanism of regeneration in order to maintain floristic diversity (Shiferaw et al 2018). With respect to invasion process, the seed bank promotes the successful establishment of alien species in new distribution ranges and support the persistence of alien species under unfavorable conditions for growth and development (Gioria et al 2012;Pysˇek et al 2015;Gioria and Pysˇek 2016;Gioria and Pysˇek 2017).…”
Section: Introductionmentioning
confidence: 99%